Damage Tolerance Analysis of Weld Joint - Aqli Mursadin; Mastiadi Tamjidillah (INFO-TEKNIK, 2001)
This research explores the development and the implementation of damage tolerance analysis on weld joints.  Two geometry types of weld joint are investigated subject to cyclic loadings.  The experimental results are used for establishing residual strength diagram and crack growth diagram for both of types.  The results show that the strength behavior may be quite different for different geometry types, even if the materials are the same.